State responsibility : the general part the general part - Crawford, James, 1948- (Cambrudge (UK) : Cambridge University Press, 2013)
"Annexed to GA Resolution 56/83 of 2001, the International Law Commission's Articles on Responsibility for Internationally Wrongful Acts put the international law of responsibility on a sound footing. As Special Rapporteur for the second reading, James Crawford helped steer it to a successful conclusion. With this book, he provides a detailed analysis of the general law of international responsibility and the place of state responsibility in particular within that framework. It serves as a companion to The International Law Commission's Articles on State Responsibility: Introduction, Text and Commentaries (Cambridge University Press, 2002) and is essential reading for scholars and practitioners concerned with issues of international responsibility, whether they arise in interstate relations, in the context of arbitration or litigation, or in bringing international claims"--provided by publisher.
$t Historical development -- $t Key concepts -- $t Corollaries of breach of an international obligation -- $t Organs and entities exercising governmental authority -- $t Direction or control by the state -- $t Other cases of attribution -- $t Breach : the material element -- $t Breach : the temporal element -- $t Circumstances precluding wrongfulness -- $t Responsibility in cases of joint or collective conduct -- $t Responsibility for breaches of communitarian norms -- $t Ancillary and secondary responsibility -- $t Succession to responsibility -- $t Restoration of legal relations after breach -- $t Reparation -- $t Remedies -- $t The claims process -- $t Claims on behalf of others : diplomatic and functional protection -- $t Implementation of responsibility by judicial process -- $t Invocation in cases involving multiple parties -- $t Implementation of responsibility by extrajudicial process. Key concepts -- Corollaries of breach of an international obligation -- Organs and entities exercising governmental authority -- Direction or control by the state -- Other cases of attribution -- Breach : the material element -- Breach : the temporal element -- Circumstances precluding wrongfulness -- Responsibility in cases of joint or collective conduct -- Responsibility for breaches of communitarian norms -- Ancillary and secondary responsibility -- Succession to responsibility -- Restoration of legal relations after breach -- Reparation -- Remedies -- The claims process -- Claims on behalf of others : diplomatic and functional protection -- Implementation of responsibility by judicial process -- Invocation in cases involving multiple parties -- Implementation of responsibility by extrajudicial process.
Includes bibliographical references (pages 778-807) and index.
Keywords: International obligations; Government liability (International law); Responsabilité de l'Etat.; Droit international; Government liability (International law); International obligations; 2; Haftung